Ritual Gwajo Neda di Kalikasa: Studi Evaluasi Kritis dalam Perspektif Soteriologi Katolik - Silverius Yohanes Pea; Antonius I. N. Tukan; Yovince Abatan (Sabar : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
This study aims to critically evaluate the Gwajo Neda ritual from the perspective of Catholic soteriology. Specifically, it seeks to examine how Catholics in Saint Anthony of Padua Parish, Kalikasa, understand the relationship between the Gwajo Neda ritual and the belief that God is the sovereign over life and death, identify the tensions between the practice of the ritual and the teachings of the Catholic faith, and formulate appropriate pastoral approaches to address these tensions. This research employed a qualitative descriptive approach, with data collected through interviews, observations, and document analysis. The findings reveal that the faithful perceive the Gwajo Neda ritual as an ancestral cultural heritage that provides emotional consolation and offers an explanation regarding the cause of a person's death. At the same time, most participants firmly believe that God alone is the source of life and the ultimate authority over life and death. Nevertheless, a theological tension arises when the ritual is regarded as the primary authority in determining the truth about death, potentially overshadowing the Christian understanding of salvation accomplished through Christ. From the perspective of Catholic soteriology, the meaning of death and salvation is rooted in the saving mystery of Christ's death and resurrection rather than in cultural ritual practices. Therefore, pastoral accompaniment is needed that both respects local cultural values and deepens the faithful's understanding of the Catholic faith through catechesis and pastoral formation, enabling cultural traditions to be lived in harmony with the teachings of the Catholic Church.